2010
DOI: 10.1167/iovs.09-3974
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/Akt and mTOR/P70S6K Signaling Pathways in Human Uveal Melanoma Cells: Interaction with B-Raf/ERK

Abstract: Activated PI3K/Akt attenuates the inhibitory effects of rapamycin on cell proliferation and thus serves as a negative feedback mechanism. This finding suggests that rapamycin is unlikely to inhibit uveal melanoma growth. In contrast, targeting PI3K while inhibiting B-Raf/ERK may be a promising approach to reduce the proliferation of uveal melanoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 44 publications
4
79
0
Order By: Relevance
“…However, MEK inhibitors cause cell-cycle arrest without significant cell death. The PI3K/AKT and mTOR/p70S6K pathways are critical for tumorigenesis, and the targeting of PI3K while inhibiting ERK has been shown to reduce the proliferation of uveal melanoma cells (8,16,17). Interestingly, we have shown that the constitutively active mutant GNAQ signals not only to ERK but also to AKT, possibly through PI3K direct binding (29) or cross talk between GPCR and receptor tyrosine kinase (RTK)-mediated signaling pathways (30,31).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, MEK inhibitors cause cell-cycle arrest without significant cell death. The PI3K/AKT and mTOR/p70S6K pathways are critical for tumorigenesis, and the targeting of PI3K while inhibiting ERK has been shown to reduce the proliferation of uveal melanoma cells (8,16,17). Interestingly, we have shown that the constitutively active mutant GNAQ signals not only to ERK but also to AKT, possibly through PI3K direct binding (29) or cross talk between GPCR and receptor tyrosine kinase (RTK)-mediated signaling pathways (30,31).…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that GNAQ binds and signals to phosphoinositide-3 kinase (PI3K; refs. [13][14][15], and that targeting PI3K/AKT pathway while inhibiting MEK/ERK is an effective approach to reduce the proliferation of uveal melanoma (8,16,17). However, the mechanisms involved in these processes are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Self-sufficiency in growth signals Gain of cell cycle stimulator-activation of pathways The PI3K-AKT prosurvival pathway is constitutively activated in UM. LOH of the PTEN locus occurs in 76% of UM [17][18][19][20][21] The RAF/MEK/ERK pathway is constitutively activated: activating mutations in GNAQ or GNA11 occur in 480% of UM and can activate the RAF/ MEK/ERK pathway 11,[22][23][24][25][26][27][28] …”
Section: The Hallmarks Of Cancermentioning
confidence: 99%
“…15 The p53 pathway is inhibited downstream to p53 in many UM, 30 and this may be a consequence of MDM2 overexpression, which is also common in UM and associated with a poor outcome. 13,15 The PI3K/AKT pathway is constitutively activated in most UM 17 (Table 1). It has been demonstrated using immunohistochemistry that phosphorylated AKT correlates with poor prognosis in UM.…”
Section: Molecular Pathway Defects In Primary Ummentioning
confidence: 99%
“…The PI3K/Akt pathway stimulates cell growth and is upregulated in cancer cells [10][11][12]. In addition, this pathway deserves further research into its role in supporting cell survival [13,14].…”
Section: Short-communicationmentioning
confidence: 99%